Effects of the internal recycling rate on biological nutrient removal and microbial community structure in a sequential anoxic/anaerobic membrane bioreactor - Ahmed, Zubair; Lim, Byung-Ran; Cho, Jinwoo; Ahn, Kyu-Hong (SPRINGER, 2007)
This study investigated the effects of the internal recycling rate on nutrients removal in a sequential anoxic/anaerobic membrane bioreactor (SAM). Microbial community structure in sludge from the SAM was studied using quinone profile method. Above 98% COD, 68% nitrogen, and 55% phosphorus removal efficiencies were achieved when the internal recycling rate was 2.5 times influent flow. At that rate, the optimum specific nitrate loading rate and COD/NO3-N ratio were found to be 2.24 mgNO(3)-N g(-1) MLSS h(-1) and 9.13, respectively. Batch tests demonstrated that anoxic condition suppressed phosphorus release, and that denitrification was also influenced by initial substrate concentration. Denitrification appeared to have some priority over phosphorus release for substrate uptake. Microbial community analysis revealed a predominance of the subclass beta-Proteobacteria. Furthermore, it was found that Rhodocyclus-related bacteria were efficient at phosphorus removal than Actinobacteria.
Keywords: WASTE-WATER TREATMENT; QUINONE PROFILE METHOD; ACTIVATED-SLUDGE; PHOSPHORUS REMOVAL; RESPIRATORY QUINONES; LIQUID-CHROMATOGRAPHY; TREATMENT PLANTS; PERFORMANCE; NITRIFICATION; SPECTROMETRY